Synthesis and antimicrobial activity of N-Mannich bases of 3-[N'- sulphadoximino] isatin and its methyl derivative - Surendra; Pandeya N.; Yogeeswari P.; Sri Ram D.; Nath G. (My University, 2025)
Schiff's bases of isatin and 5-methyl isatin with sulphadoxine and then its n-Mannich bases were synthesised and evaluated for their anti-microbial activity. The piperidonemethyl group improved the activity and most of the compounds were more potent than the pure drugs.